Juridical Analysis of The Role of The Investment Law in Promoting National Economic Growth and Stability - Ibrahim, Muhamad Sidik Ajib; Malau, Parningotan; Salmah, Salmah; Silitonga, Christopher EF (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Investment plays a crucial role in promoting economic growth and maintaining national economic stability, especially in the context of globalization, which demands legal certainty and a conducive investment climate. This study is driven by the need to evaluate the effectiveness of Law Number 25 of 2007 concerning Investment as a legal instrument for strengthening the foundation of national economic development. The main issue examined is how the normative role of the Investment Law contributes to creating a healthy and sustainable investment climate. This research employs a normative juridical method using the statute approach and conceptual approach, focusing on the analysis of applicable regulations and relevant legal doctrines. The results of the study indicate that, normatively, the Investment Law provides legal certainty for investors. However, its implementation still faces several challenges, including regulatory overlap across sectors and weak institutional coordination. Therefore, regulatory harmonization and institutional strengthening are essential to ensure that the law effectively supports sustainable economic growth and national stability.